Black Jews in Africa and the Americas - Parfitt, Tudor (Harvard University Press, 2012)
Black Jews in Africa and the Americas tells the fascinating story of how the Ashanti, Tutsi, Igbo, Zulu, Beta Israel, Maasai, and many other African peoples came to think of themselves as descendants of the ancient tribes of Israel. Pursuing medieval and modern European race narratives over a millennium in which not only were Jews cast as black but black Africans were cast as Jews, Tudor Parfitt reveals a complex history of the interaction between religious and racial labels and their political uses. For centuries, colonialists, travelers, and missionaries, in an attempt to explain and understand the strange people they encountered on the colonial frontier, labeled an astonishing array of African tribes, languages, and cultures as Hebrew, Jewish, or Israelite. Africans themselves came to adopt these identities as their own, invoking their shared histories of oppression, imagined blood-lines, and common traditional practices as proof of a racial relationship to Jews. Beginning in the post-slavery era, contacts between black Jews in America and their counterparts in Africa created powerful and ever-growing networks of black Jews who struggled against racism and colonialism. A community whose claims are denied by many, black Jews have developed a strong sense of who they are as a unique people. In Parfitt's telling, forces of prejudice and the desire for new racial, redemptive identities converge, illuminating Jewish and black history alike in novel and unexplored ways.